2018
DOI: 10.1093/ibd/izy007
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Signaling and Metabolism Gene Signature in Pediatric Inflammatory Bowel Disease: A Matched-case Control Pilot Study

Abstract: Goal The aim of this study was to investigate gene expression levels of proteins involved in sphingosine-1-phosphate (S1P) metabolism and signaling in a pediatric inflammatory bowel disease (IBD) patient population. Background IBD is a debilitating disease affecting 0.4% of the US population. The incidence of IBD in childhood is rising. Identifying effective targeted therapies that can be used safely in young patients and developing tools for selecting specific candidates for targeted therapies are important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 52 publications
(59 reference statements)
2
24
0
2
Order By: Relevance
“…Downregulated S1P (d16:1) might indicate a shortage of S1P. The result is consistent with a recently published case-control pilot study [43], which determined the whole sphingolipid profiles and S1P-related gene expression in the colon tissues of IBD patients. The results identified an association between elevated transcriptomic signatures and active IBD status, which were normalized in remission cases.…”
Section: Discussionsupporting
confidence: 91%
“…Downregulated S1P (d16:1) might indicate a shortage of S1P. The result is consistent with a recently published case-control pilot study [43], which determined the whole sphingolipid profiles and S1P-related gene expression in the colon tissues of IBD patients. The results identified an association between elevated transcriptomic signatures and active IBD status, which were normalized in remission cases.…”
Section: Discussionsupporting
confidence: 91%
“…The critical findings of this study showed an upregulation of S1P synthetic genes (SphK1, SphK2), signaling (S1PR1, S1PR2, S1PR4) and degradation (SGPL1) in colon biopsies of IBD patients with moderate to severe symptoms compared to control or patients in remission. Ceramide and ceramide 1-phosphate (C1P) levels were significantly elevated in IBD patients compared to control [232].…”
Section: A Role Of S1p In Gastrointestinal Diseasesmentioning
confidence: 99%
“…S1P is involved in several diseases like cancer, 31 inflammatory bowel disease, 32 chronic kidney diseases, and multiple sclerosis. 33 Recently, it has been shown that S1P also plays a role in GO by promoting inflammation, 28 adipogenesis, 26 and fibrosis.…”
Section: Discussionmentioning
confidence: 99%